Developing Scotland’s First Green Health Prescription Pathway: A One-Stop Shop for Nature-Based Intervention Referrals - Marx, Viola; More, Kimberly R. (Frontiers in Psychology, 2022)
Introduction. Lifestyle modifications are part of comprehensive treatment plans to help manage the symptoms of pre-existing chronic conditions. However, behaviour change is notoriously difficult as patients often lack the necessary support. The present paper outlines the development of a Green Health Prescription programme that was designed to link patients with appropriate lifestyle interventions (i.e. nature-based interventions) and to support attendance. Method. Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was undertaken in three focus groups (i.e., National Health Service healthcare professionals, service-users, and nature-based intervention delivery partners) to highlight areas of strength and weakness within the proposed programme prior to delivery. Results. SWOT analysis revealed that the programme was supported by all three focus groups. Weaknesses and threats were identified including sustainability of nature-based interventions in terms of funding, the need to connect patients with appropriate interventions based on their physical and mental health needs, and the requirement to have a ‘one-stop shop’ for information to ensure that the programme was accessible for all service-users and healthcare professionals. Results were addressed and considered throughout the development of the programme. Discussion. The Green Health Prescription programme was launched in 2019 and gave patients the ability to receive a prescription from a healthcare professional, community service, or to self-refer. The programme allows patients to contact a consultant, via a telephone service, who is trained to match them with a programme that the patient believes will be enjoyable and that fits their treatment needs. Data collection to assess the efficacy of the programme is ongoing.